Facilities and Infrastructure Management in an Islamic Boarding School: A Case Study of Pesantren Darullughah Wadda'wah, Pasuruan - Akhmad Fauzi Hamzah (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2026)
Management of facilities and infrastructure in Islamic boarding schools is a crucial factor in supporting the quality of education, but academic studies in this area are still limited. This study aims to analyze the implementation of facility and infrastructure management at Dalwa Islamic Boarding School based on Islamic values, describe its management cycle, identify challenges and opportunities, and formulate an integrated management model. The study used a qualitative approach with a case study design. The results show that Dalwa Islamic Boarding School has internalized Islamic values ​​(amanah, ikhlas, efficiency, anti-israf, and maslahah) in the management of facilities and infrastructure. The management cycle includes six continuous stages: planning through annual deliberations, procurement based on the best specifications, distribution, use with an orderly schedule, preventive and educational maintenance involving students, and disposal of assets through transparent and documented procedures. Challenges faced include limited competent human resources, a suboptimal documentation system, tensions between tradition and modernization, and demands for environmental sustainability. Available opportunities include the adoption of information technology, strategic partnerships with the government and corporations, and the development of a green Islamic boarding school model. This study proposes a Values-Based and Technology-Based Infrastructure Management (MSPBNT) model supported by three pillars: integration of Islamic values, a structured management system, and adoption of information technology. This model is expected to serve as a reference for Islamic boarding schools (pesantren) in managing facilities and infrastructure effectively, efficiently, accountably, and in an educational and Islamic manner.